Cryptosporidium as a common cause of childhood diarrhoea in Italy. - Caprioli, A. (Cambridge University Press, 1989)
Cryptosporidium oocysts were observed in the stools of 9 (7.2%) of 124 Italian children with diarrhoea, examined during the period 1 January-31 December 1984. In two children, the parasite was associated with other enteric pathogens. The duration of diarrhoea was 2-30 days, with a median of 6 days. In all cases the infection was self limiting. The mean age of the Cryptosporidium-positive children was 34 months, and all cases occurred in the warm season. Cryptosporidium was found to be the third most common enteric pathogen after rotavirus and Salmonella spp.